Seroprevalence and incidence of primary dengue infection and its correlation with fetomaternal prognosis in Western Rajasthan - Prabhu Prakash; Ekta Gupta; Pooja Nareda; Eshank Gupta; Richa Agarwal; Vishakha Ashopa; Anjali Beelwal (Journal of Family Medicine and Primary Care, 2023)
Background: Viral hemorrhagic fevers are becoming increasingly common in the tropics and subtropics. Dengue fever is currently the most important arthropod-borne viral disease because of its widespread distribution in more than 100 countries and its potential for extensive outbreaks of life-threatening disease. Material and Methods: This study was a hospital-based cross-sectional study conducted in the Microbiology Laboratory of Maternal and Child Tertiary Care Hospital in Western Rajasthan, India, between January 2021 and December 2021. Institutional Ethical Committee permission was obtained. All patients with clinical suspicion of dengue-like illness (DLI), attending outpatient department (OPD) or inpatient department (IPD), were included in the study after obtaining their written consent. A blood sample was collected, and the Dengue Duo rapid card test was conducted for the detection of nonstructural protein 1 (NS1) antigen and immunoglobulin (Ig) M or IgG antibody estimation. All positive samples were tested for IgM enzyme-linked immunosorbent assay (ELISA) test using MAC-ELISA. Results: Of 250 positive sample, the distribution of cases as per clinical features was as follows: all cases presented with fever (100%) followed by myalgia (24.5%), headache (16.06%), hemorrhagic manifestation (13.25%), rash (8.84%), and bleeding gums (2.01%). Thrombocytopenia was seen in 30.40% (76/250) of dengue fever cases. NS1 antigen was detected in 157 cases (62.80%) followed by IgG in 84 cases (33.60%), IgM in 77 cases (30.80%), NS1+IgG in 27 cases (10.80%), NS1 + IgM in 16 cases (6.40%), and NS1 + IgM + IgG in five cases (2%). Of 250 samples, 77 cases were IgM positive and 173 were IgM negative by the Dengue Duo card test. Among the 173 Dengue Duo IgM card negative, 131 cases (79.39%) were also detected negative by IgM ELISA and 42 cases (49.41%) were detected positive by IgM ELISA. The sensitivity was 50.59%, the specificity was 79.39%, the positive predictive value (PPV) was 55.84%, the negative predictive value (NPV) was 75.72%, and the diagnostic accuracy was 69.90%. The case fatality of the cases was 2.35%. Conclusion: Early diagnosis and treatment can prevent mortality in pediatric and pregnant females suffering from dengue and dengue-like illness. Facility and availability of ELISA kits should be adequate for early confirmation of suspected dengue patients by ELISA test.